2020
DOI: 10.4067/s0719-81322020000300095
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers of endothelial glycocalyx injury in canine parvoviral infection

Abstract: Canine parvoviral enteritis (PVE) is one of the most common diseases in young dogs. A range of diseases and inflammatory conditions can cause endothelial glycocalyx (eGCX) disruption, therefore, this study aimed to determine the presence of eGCX damage in dogs with PVE using serum biomarkers of eGCX, and to evaluate their prognostic importance among survivor and non-survivor dogs. Twenty dogs diagnosed with PVE and 10 healthy dogs of both sexes, mixed-breed, and under 6 months of age were included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“… Lawrence-Mills et al (2022b) Hypercoagulability; MMVD Plasma HA Increased plasma HA was found in dogs with hypercoagulability as well as dogs with MMVD. Naseri et al (2020) Canine parvoviral enteritis Serum ESM-1 Higher serum ESM-1 was found in non-survivors. Yini et al (2015) Septic shock model Plasma syndecan-1 and HS Increased plasma syndecan-1 and HS was found following injection with a lethal dose of E. coli .…”
Section: Evidence For Eglx Involvement In Diseasementioning
confidence: 99%
See 2 more Smart Citations
“… Lawrence-Mills et al (2022b) Hypercoagulability; MMVD Plasma HA Increased plasma HA was found in dogs with hypercoagulability as well as dogs with MMVD. Naseri et al (2020) Canine parvoviral enteritis Serum ESM-1 Higher serum ESM-1 was found in non-survivors. Yini et al (2015) Septic shock model Plasma syndecan-1 and HS Increased plasma syndecan-1 and HS was found following injection with a lethal dose of E. coli .…”
Section: Evidence For Eglx Involvement In Diseasementioning
confidence: 99%
“…The same study identified relationships between serum interleukin (IL)− 6 and hyaluronan concentrations, suggesting an association between inflammation and eGlx degradation. In dogs with parvoviral enteritis, circulating endothelial cell-specific molecule-1 concentrations were increased compared to controls ( Naseri et al, 2020 ) suggesting endothelial cell injury. However, the eGlx components syndecan-1 and heparan sulfate, were not found to be significantly different between affected dogs and controls ( Naseri et al, 2020 ).…”
Section: Evidence For Eglx Involvement In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This allows more fluid to leak from compromised blood vessels, exacerbates interstitial edema, and triggers intravascular coagulation [ 6 8 ]. In previous studies, conditions such as septic peritonitis and parvoviral infections have been associated with eGCX damage in dogs [ 9 , 10 ]. Human studies have shown that conditions such as hypertension, hypercholesterolemia, cardiovascular disease, chronic kidney disease, diabetes, atherosclerosis, hypervolemia (aggressive fluid resuscitation), and ischemia–reperfusion injury can also lead to eGCX degradation [ 11 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the four indicators, only serum ESM-1 concentratoin was significantly associated with parvoviral infection and a lower survival rate. Based on these results, ESM-1 could be utilized as a prognostic factor for diseases that cause inflammation and eGCX damage, such as parvoviral enteritis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%